Mathematical Accommodations for Students with Autism Spectrum and Attention Deficit Hyperactivity Disorders: International Comparisons of Education Disparities - Gallardo Herrerías, Celia (2025)
This international comparative study examines arithmetic instruction accommodations for students with Autism Spectrum Disorder (ASD), Attention Deficit Hyperactivity Disorder (ADHD), and co-morbidities. In ten countries, the research discovers differences in policy support, teacher training, and access to materials. Implications are that although high-resource nations have organized inclusive practices supported by professional development, lower-resource countries utilize unstructured, incoherent practices. Most notably, student accommodations for ASD and ADHD co-occurring are non-existent, which reflects an imperative lacking space in inclusive pedagogy. There are contributions to the effectiveness of arithmetic pedagogy from cultural, institutional, and socio-economic contexts. This study emphasizes the requirement for targeted, scalable, and culture-sensitive interventions that include math education as a social justice and equity imperative.